2002
DOI: 10.1524/ract.2002.90.4_2002.205
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aggregation on the extraction of trivalent lanthanide and actinide cations by purified Cyanex 272, Cyanex 301, and Cyanex 302

Abstract: Extraction / Cyanex / Aggregation / Americium / CuriumSummary. The extraction of trivalent lanthanide (Sm 3+ , Eu 3+ ) and actinide (Am 3+ , Cm 3+ ) cations from 1.0 M NaNO 3 into n-dodecane solutions of bis(2,4,4-trimethylpentyl)phosphinic acid (HC272), bis(2,4,4-trimethylpentyl)monothiophosphinic acid (HC302), and bis(2,4,4-trimethylpentyl)dithiophosphinic acid (HC301) is reported. In each case, the dependence of the distribution ratios on the total extractant concentration is approximately second power. Usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(75 citation statements)
references
References 36 publications
3
70
2
Order By: Relevance
“…The most successful approaches to group separations developed to date have involved exploiting the slightly greater covalency of An 3þ -bonding interactions, which was first reported by Diamond et al [3]. This difference in bonding characteristics is coincident with the greater radial extension of the 5f orbitals (relative to the 4f orbitals in the lanthanides), though it is not yet clear that the effect is indicative of 6d orbital participation in metal-ligand bonding [4][5][6][7]. Interaction of nitrogen and sulfur donors with An 3þ is stronger than with Ln 3þ , thus potentially enabling a successful separation [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most successful approaches to group separations developed to date have involved exploiting the slightly greater covalency of An 3þ -bonding interactions, which was first reported by Diamond et al [3]. This difference in bonding characteristics is coincident with the greater radial extension of the 5f orbitals (relative to the 4f orbitals in the lanthanides), though it is not yet clear that the effect is indicative of 6d orbital participation in metal-ligand bonding [4][5][6][7]. Interaction of nitrogen and sulfur donors with An 3þ is stronger than with Ln 3þ , thus potentially enabling a successful separation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Interaction of nitrogen and sulfur donors with An 3þ is stronger than with Ln 3þ , thus potentially enabling a successful separation [5]. This fundamental difference has inspired considerable research addressing the development of soft donor molecules or ions for separations applications [4,[7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14][15][16] The use of vapor pressure osmometry to examine unpurified Cyanex 301/heptane solutions has revealed that the extractant is present in monomeric form in the concentration range of 0.016-0.16 M. [12] However, J. Chen et. al., [13] using an interfacial distribution method for the aqueous and organic phases, demonstrated that pure Cyanex 301 is dimeric in heptane solutions in the concentration range of 0.2-1.0 M (pH 5 3.66).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is well known that the trivalent lanthanide and actinide ions possess about 8−9 molecules of water in the inner coordination sphere depending on the cation size. It is, however, reasonable to assume that about 9 water molecules are present in the inner coordination sphere of Am 3+ as well as Eu 3+ (18). Therefore, while forming the extractable complexes, the inner-sphere water molecules get replaced by the extractants, Cyanex 301 and terpy in the present case, to yield hydrophobic complexes which are easily extracted.…”
Section: Determination Of Thermodynamic Parametersmentioning
confidence: 85%